Simulation Based Exploration of Stock Market Using LSTM Model - Tetarwal, Rohit; Tushir, Rohit (International Journal of Computer Sciences and Engineering, 2023)
In today’s world the stock market has a huge impact on the economy making it difficult for stock market investors to predict stock prices. Financial market investors cannot use simple models to more accurately predict stock prices to invest in stocks. Deep learning helps computer to solve complex problems which humans takes more time to solve. This paper is based on developing a model to predict inventory value using recurrent neural network (RNN) and long- short term memory model (LSTM).